Evaluation of pd-1, pd-l1, and cytotoxic T-lymphocyte associated protein 4 expressions together with clinicopathological findings in clear cell, papillary, and chromophobe types of renal cell carcinoma - Inceman, Merve; Toyran, Tugba; Bayazit, Yildirim; Izol, Volkan; Erdogan, Seyda (Polish Journal of Pathology, 2022)
Our study aimed to determine the expressions of programmed death protein 1 (PD-1), programmed death ligand protein 1 (PD-L1), and cytotoxic T-lymphocyte- associated protein 4 (CTLA-4) to investigate and compare the differences between early and advanced cases in the 3 most common types of renal cell carcinoma (RCC) and reveal their correlations with prognosis and survival. A total of 166 RCC cases diagnosed between 2010 and 2019 in our hospital were included. PD-1, PD-L1, and CTLA-4 markers were applied to the paraffin blocks of the cases using an immunohistochemical method, and their expression status was evaluated by distinguishing subtypes in advanced- and early-stage RCCs. It was observed that PD-L1 positivity in the tumour cells, in clear cell RCC, was statistically significantly more frequent in advanced-stage cases compared to early-stage cases. It was concluded that cases with PD-L1 positivity in tumour- infiltrating mononuclear cells (TIMC) in clear cell and chromophobe RCC had a shorter survival. The frequency of perinephritic fat invasion and necrosis was higher in cases with PD-L1 expression in TIMC. We think that PD-1, PD-L1, and CTLA-4 must be considered together in advanced stage RCC for the treatment of both pathway inhibitors. Further large studies will shed light on the immunotherapy options at the advanced stage of all RCC types even in the absence of metastasis.